The Prevalence of Insufficient Sleep and Bedtime Delay Among Kindergarten Children Aged 3 to 6 Years in a Rural Area of Shanghai: A Cross-Sectional Study - Xi Chen; Yan Qiang; Xia Liu; Qing Yang; Qingqing Zhu; Bin Li; Ruiping Wang (Frontiers Media S.A., 2021)
Introduction: Sleep deprivation in children is a global public health problem that affects the physical and mental development of children. Bedtime delay induced by longer screen time and heavy study load is a common cause of sleep deprivation in children. However, the prevalence of insufficient sleep and bedtime delay and related influencing factors among kindergarten children is limited in Shanghai, China.Methods: In 2018, we selected 8,586 children aged 3 to 6 years and their parents in Songjiang District, Shanghai. Data was collected among parents by face-to-face questionnaire interview with signed informed consent. We defined insufficient sleep as those who slept for < 10 h in children aged 3-5 years or 9 h in children aged 6 years within 24 h, and we define bedtime delay as children with bedtime after 21:00. SAS 9.1.3 software was used to calculate the prevalence of bedtime delay and insufficient sleep, and logistic regression was used to explore potential influencing factors.Results: The prevalence of insufficient sleep and bedtime delay among children aged 3 to 6 years was 11.67 and 56.85%, respectively. The prevalence of insufficient sleep among boys was slightly higher than among girls [odds ratio (OR) = 1.18, 95% confidence interval (CI): 1.04-1.35]. With the increase of the age of children, the prevalence of insufficient sleep increased gradually (P < 0.05). The prevalence of insufficient sleep was higher among the only child in the family (OR = 1.18, 95% CI: 1.02-1.36) and those with longer hours of TV watching (OR = 109, 95% CI: 1.02-1.16). Meanwhile, the prevalence of bedtime delay was also higher among the only child in the family (OR = 1.17, 95% CI: 1.06-1.79), among those with parents accompanying for sleep (OR = 1.21, 95% CI: 1.10-1.34), and those with longer TV watching time (OR = 1.13, 95% CI: 1.07-1.18).Conclusions: Insufficient sleep and bedtime delay were prevalent in Chinese children aged 3 to 6 years, especially in boys and older children. TV watching as well as parents accompanying for sleep were associated with insufficient sleep and bedtime delay. We recommend that parents should limit the screen time of children, advocate earlier bedtime and later morning wake-up among children, as well as make their children sleep in separate beds or rooms in younger age.